Mapping of Indian bread wheat population, HD 2189 × Agra Local for adult plant leaf rust resistance, Lr34 - and PRIYAMVADA, M.S. SAHARAN*, R. TIWARI, SIMON G. KRATTINGER, B. KELLER (Indian Phytopathology, 2012)
To identify and map quantitative trait loci (QTLs) for leaf rust resistance, 128 single seed descent lines of an ‘HD2189’×‘Agra Local’ F6 population were analyzed with molecular markers. Percent leaf area infected and the response to infection recorded in two field trials in 2006-07 at Karnal (India) were transformed to the area under the disease progress curve (AUDPC). Above 128 recombinant inbred lines along with parental lines were analysed with six polymorphic simple sequence repeats (SSRs) markers (GWM1220, XWM1, SWM5, SWM8, SWM10 & WMC463) and one sequence tagged sites (STS) marker, csLV34. A genetic linkage map based on above markers data was established. The region containing Lr34 was flanked by XSWM8 (proximal) and XWMC463 (distal) and spanned 68.7 CM in ‘HD 2189’×‘Agra Local’ population. Marker SWM10 was closely located to Lr34 in present population. By using composite interval mapping and LOD >4.4, QTL analysis of the linkage group representing chromosome 7DS in the HD 2189×Agra Local population defined a QTL for leaf rust resistance in the interval XGWM1220 - XSWM10 which accounted for 14.8 % of observed phenotypic variation.